THE ROLE OF THE NATIONAL BANK IN CREATION OF PUBLIC DEBT OF INDEPENDENT KINGDOM OF SERBIA - Krstić, Snežana; Vukša, Slavko; Andžić, Slobodan (Economics of Agriculture, 2012)
The time characterized by a public debt phenomenon in modern Serbia has been attached to the end of the XIX and the beginning of the XX Century, when the battle for independence had caused growth of Serbian foreign debt. It is considered that the states contraction of debts at the National Bank4 has been old as well as the National Bank institution by its self. In other words, more before the Serbian National Banks counters were opened, there was made the state debt by approving the loan of 304,216 dinars in gold, on backing of the state treasury bills. Therefore was made the initial business transaction of the bank, which was done before its regular business activities.